Export Competitiveness of Indonesian Cocoa Commodities and Derivative Products in the International Market in Conditions Before and After the Export Duty Determination - Tupamahu, Yonette Maya; Apituley, Margaretha Rosalyn (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
This study aims to analyze the competitiveness of Indonesian cocoa commodities and their derivatives before and after the implementation of export duties in Indonesia. The data used is for the period before 2000-2009 and the period after 2010-2020. The method used is the analysis of the RSCA Index and the Trade Specialization Index (TSI). The research results show an analysis of competitiveness based on: (1) RSCA Index: In the previous condition, Indonesia was an exporter and had competitiveness in the commodities of cocoa beans, cocoa butter and cocoa powder, while cocoa paste did not have competitiveness. In the following conditions, the commodities whose competitiveness decreased were cocoa beans and cocoa powder, the commodities whose competitiveness increased were cocoa paste, and the commodities whose competitiveness remained strong were cocoa butter. (2) TS Index: in the previous conditions, Indonesia was an exporting country for the commodities of cocoa beans, cocoa butter, cocoa paste and cocoa powder. In the following conditions, Indonesia is an importing country for cocoa bean commodities, while Indonesia remains an exporting country for cocoa butter, cocoa paste and cocoa powder.